THE ROLE OF METAPHOR IN FORMING THE LANGUAGE OF NATIONALSCIENCE - Userbay Alimhanovich Baykabilov (Western European Studies, 2024)
Understanding a metaphor means observing how it is created mentally to a certain extent, and this requires mental strength and the formation of semantic harmony in order to overcome incompatible meanings
Keywords: metaphor; trope; nominative case; creative